Pendekatan Saintifik Melalui Media Audiovisual Berbasis Pendidikan Karakter untuk Meningkatkan Kemampuan Berpikir Kritis dan Hasil Belajar Materi Iman Kepada Hari Akhir pada Siswa Kelas IXD SMP Negeri 1 Gabus Kabupaten Grobogan Tahun Pelajaran 2019/2020: Array - Sutrisno (eductum: Jurnal Literasi Pendidikan, 2022)
The purpose of this classroom action research is to improve critical thinking skills and learning outcomes in class IXD students at SMP Negeri 1 Gabus, Grobogan Regency. This research is a classroom action research carried out in two cycles, namely cycle I and cycle II. Each cycle consists of planning, action, observation, and reflection. Data collection uses test and non-test techniques. The tests are carried out in the form of written tests for learning outcomes, non-tes are applied through questionnaires, observations, teacher journals, student journals, interviews, and photo documentation. The data analysis technique used is quantitative and qualitative analysis. The observation results of the ability to think critically in the first cycle showed an average value of 59.91, which was categorized as not critical, in cycle II, it increased to 72, which was categorized as quite critical. The increase in cycle I to cycle II reached 30%. The learning outcomes in cycle I was 74.92 which was included in the sufficient category in cycle II, which increased by 86.33% in the good category in cycle II. Based on these results it can be concluded that the use of a scientific approach through audiovisual media based on character education has been implemented well so that it can improve the process of improving learning, spiritual attitudes, social attitudes, critical thinking skills and learning outcomes in class IXD students at SMP Negeri 1 Gabus, Grobogan Regency and provide positive effect.